Peluang dan Tantangan Paradiplomasi sebagai Jembatan Akselerasi Pembangunan di Kota Tidore Kepulauan - Arisanti, Desi (PT. Sangadji Media Publishing, 2025)
Paradiplomacy serves as a crucial instrument for strengthening regional capacities to engage globally and accelerate development based on local potential. This study aims to analyze the role of paradiplomacy as a bridge for accelerating development in the City of Tidore Kepulauan, focusing on its opportunities, challenges, and strategic policy directions for sustainable implementation. The study adopts a qualitative descriptive approach, employing literature review and limited field observation as data collection techniques. Data were analyzed through the reduction, display, and conclusion-drawing stages, and validated through source triangulation. The results reveal that paradiplomacy in the City of Tidore Kepulauan holds significant potential to enhance international cooperation in historical tourism, education, environmental management, and local investment. Cultural diplomacy initiatives—such as collaboration with the Embassy of Spain and the City of Seville—demonstrate concrete efforts to promote history-based regional diplomacy. However, the findings also indicate several structural challenges, including limited institutional capacity, inadequate human resources, and weak policy integration between local and central governments. Therefore, strengthening local diplomatic institutions, improving bureaucratic competencies, and ensuring multi-level policy synergy are essential prerequisites for effective paradiplomacy governance. These findings are expected to contribute both academically and practically by providing strategic insights for regional governments in designing adaptive and sustainable paradiplomacy policies.